2016
DOI: 10.1093/aje/kwv231
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Dietary Long-Chain ω-3 Polyunsaturated Fatty Acids and Fish Consumption With Endometrial Cancer Risk in the Black Women's Health Study

Abstract: Dietary long-chain (LC) ω-3 polyunsaturated fatty acids (PUFAs), which derive primarily from intakes of fatty fish, are thought to inhibit inflammation and de novo estrogen synthesis. This study prospectively examined the associations of dietary LC ω-3 PUFAs and fish with endometrial cancer risk in 47,602 African-American women living in the United States, aged 21-69 years at baseline in 1995, and followed them until 2013 (n = 282 cases). Multivariable-adjusted Cox regression models estimated hazard ratios and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…Fernandez et al reported a dose-response relationship between fish consumption and decreased endometrial cancer risk [ 13 ]. However, such a significant association was not detected in other studies [ 16 , 18 23 ]. In two other studies conducted in Asia, high fish consumption was detected to confer an increased risk of developing endometrial cancer [ 24 , 25 ].…”
Section: Introductioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Fernandez et al reported a dose-response relationship between fish consumption and decreased endometrial cancer risk [ 13 ]. However, such a significant association was not detected in other studies [ 16 , 18 23 ]. In two other studies conducted in Asia, high fish consumption was detected to confer an increased risk of developing endometrial cancer [ 24 , 25 ].…”
Section: Introductioncontrasting
confidence: 59%
“…Twelve studies reported the association of fish consumption with endometrial cancer risk comparing the highest category with the lowest category [ 14 16 , 18 22 , 24 , 25 , 28 , 31 ]. After pooling the results of these studies, we did not detect a significant association between the highest vs .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, European and Asian cohorts have recorded possible risk reduction of colorectal and breast cancers with omega-3 fish consumption [48,49], but more research is needed in Blacks. Brasky et al found no significant association between omega-3 and fish consumption and endometrial cancer risk in 47,602 African American women, although non-significant hazard ratios were more favorable among normal weight women (HR = 0.53; 95% CI = 0.18, 1.58) than in overweight women (HR = 0.88; 95% CI = 0.56, 1.31) [50].…”
Section: Cancermentioning
confidence: 99%